WOMAN FAITHFULNESS IN LONE SCHERFIG'S ONE DAY MOVIE (2011): AS A READER RESPONSE STUDY - Vera Ananda Kharisma; Teguh Kasprabowo (Dinamika Bahasa dan Budaya, 2021)
Relationship is the continuity of interaction between two or more people that can easily make the process of recognizing one another. Relationships occur in every process of human life. Relationships can be divided into relationships with peers, parents, family, and the social environment. Most people desire a relationship that consists of two partners who only have eyes for each other. Yet, many people enter relationships with the intention of being faithful and end up straying. Faithfulness requires communication and concentrated effort from both partners. Faithfulness is defined differently across relationships. The aim of this research is to figure out how faithful woman is in a relationship and how they maintain to be faithful. Based on the analysis of One Day movie (2011) uses reader response theory by Louis Rosenblatt. From the reader response theory by Louis Rosenblatt, the researcher analyze the subject use the knowledge, feeling and emotion. The researcher collect the data by seeing the movie, reads the screenplay, then interpreting the data, and analyzed it. The result of this study explained how women maintain to be faithful by their actions in keeping good communication, showing interest and being patient. The causes of faithfulness were the feeling of deep love, the length of relationship and comfortable feeling with partner. And there were positive impacts and negative impacts in being faithful.